Cognition impairment of rat in undersea environment. Issue 4 (3rd April 2022) - Zou, Yingxin; Tang, Ying; Fan, Wei; Liu, Lina; Jiao, Yong
ABSTRACT: This study was designed to examine the cognitive responses of rat simulation model of the undersea environment. Rats were randomized into five groups: control, restraint, hyperbaric air, restraint with hyperbaric air, and restraint with hyperbaric air and immersion The cognition functions were assessed by Morris water maze test and forced swimming test. The cerebral blood flow (CBF) was monitored. The parameters examined were total antioxidant capacity (TAC), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-px), glutathione (GSH), glutathione reductase (GR), and malondialdehyde (MDA). It was observed that the rats in the experimental groups had impaired learning and memory and behavioral despair accompanied by increase in CBF and MDA levels but decrease of TAC, SOD, CAT, GSH-px, GSH, and GR levels. These indicated that the simulated underwater conditions might cause immediate and transient cognition impairment in the rat models. The simulated environment induced oxidative stress led to the negative cognitive changes.